Green Chemical Processes : Developments in Science, Math, Engineering and Technology - Al-Abadleh, Hind A.; Benvenuto, Mark Anthony; Chen, Huan; Chow, Alex T.; Claveau, Emily E.; Guron, Marta; Haisha, Jewels; Islami, Eliona; Kolopajlo, Larry; Kolopajlo, Lawrence; Wilson, Angela K. (Green Chemical Processing ,, 2024)
A volume that includes examples of the newest ideas and practices how green chemistry and green science can be applied - in the classroom, but also in the connections between classes and the work place. In this volume brings together authors who are making novel strides in bringing green chemistry principles in their teaching and their work.